Plate 102: Device for two men to drain water from a foundation - Ramelli, Agostino (Le diverse et artificiose machine del capitano Agostino Ramelli, 1588)
Mechanics: hand crank; force pump; spur gear and lantern; spur gear and rack.
Keywords: Pumping machinery; Reciprocating pumps; Machinery; Hand pumps